PROTECT YOUR SMILE: ESSENTIAL MOUTH HYGIENE HABITS YOU NEED TO KNOW" - Kushakova Venera Abdurazzakovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Maintaining proper mouth hygiene is essential not only for a bright, confident smile but also for overall health. This article offers a comprehensive guide on the importance of oral hygiene, outlining daily habits like brushing, flossing, and using mouthwash. It delves into the role of diet in oral health and provides expert tips on avoiding common mistakes that lead to cavities, gum disease, and bad breath. The article also addresses the lesser-known benefits of good mouth hygiene, such as its impact on heart health and its role in preventing oral infections. Through practical advice and scientific insights, readers will learn how simple yet effective routines can keep their mouth clean and healthy for a lifetime.